Therapeutic potential of multifunctional myricetin for treatment of type 2 diabetes mellitus - Niisato, Naomi; Marunaka, Yoshinori (Frontiers in Nutrition, 2023)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by chronic hyperglycemia, insulin resistance, and insufficient insulin secretion. It is considered that chronic hyperglycemia causes serious problems due to diabetic complications such as retinopathy, nephropathy, and neuropathy. Primarily, treatment in T2DM is pharmacologically tried by using drugs that are insulin sensitizers, insulin secretagogues, α-glucosidase inhibitors, and glucose transporter inhibitors. However, long-term application of these drugs frequently induces various harmful side effects, suggesting that the importance of taking advantage of natural products like phytochemicals. Accordingly, flavonoids, a group of phytochemicals, have attracted attention as components of natural products which are effective in the treatment of several diseases containing T2DM and are strongly recommended as food supplements to ameliorate T2DM-related complications. Several well-studied flavonoids such as quercetin and catechin are known to have anti-diabetic, anti-obesity, and anti-hypertensive actions, although a huge number of flavonoids are still under investigation and their actions are not fully understood. In this situation, myricetin is being shown to be a multiple bioactive compound to prevent and/or suppress hyperglycemia through inhibiting digestion and uptake of saccharides and enhancing insulin secretion as a possible GLP-1 receptor agonist, and to ameliorate T2DM-related complications by protecting endothelial cells from oxidative stress induced by hyperglycemia. In this review, we summarize the multiple effects of myricetin on the targets of T2DM treatment, comparing with different flavonoids.